The President, the Hero: Politics of Strength, Health, and Success surrounding Donald Trump’s COVID-19 Infection - Kolehmainen Pekka M. (Filmiverkko ry, 2025)
This article examines Donald Trump’s COVID infection as a media event where the President and his supporters in right-leaning media participated in a mediated performance, seeking to present their own interpretation as the dominant narrative. I trace how the President and his supporters seized on the opportunity to narrativize Trump’s COVID-19 infection for the purpose of political messaging in the 2020 election. Specifically, I contextualize the ideological narratives produced by Trump and his allies within the larger context of U.S. conservatism and its relationship to the politics of strength, health, and success. I argue that the media performance by the President and his supporters looked to elevate Trump as a hero figure, with his infection representing a sacrifice that he had undertaken for the sake of the nation.